THE HYDROLYSIS PROCESS OF COMPOSITE COAGULANTS, THE FORMATION OF POLYNUCLEAR HYDROXO-COMPLEXES AND THEIR COAGULATION ACTIVITY (Symposium on Life and Environmental Sciences, 2026)
This thesis studies the hydrolysis of the aluminium and iron(III) salts within the composite coagulant, the formation of polynuclear hydroxo-complexes and their coagulation activity. Hydrolysis is multistage and develops from mononuclear hydroxo-complexes to polynuclear species, in particular the Keggin structure Al₁₃O₄(OH)₂₄(H₂O)₁₂⁷⁺ (Al₁₃). By the Ferron method the species were resolved into mononuclear (Al_a), polynuclear (Al_b) and colloidal-precipitate (Al_c) fractions. The polynuclear Al₁₃ fraction exhibited the highest coagulation activity, since its high positive charge and size combine charge neutralisation with bridging. At a basicity B = [OH]/[Me] ≈ 1.8–2.2 the Al₁₃ content was maximal (≈ 70 %) and turbidity removal reached 96.4 %. The results justify the advantage of pre-hydrolysed reagents.
Keywords: Hydrolysis, polynuclear hydroxo-complex, Keggin structure, Al₁₃, Ferron method, basicity, charge neutralisation, coagulation activity, speciation, pH.